The organizational climate and its association with job satisfaction in a higher education institution - Soria Reséndez, Ana Cristina; Pedraza Melo, Norma Angélica; Bernal González, Idolina (Acta Universitaria, 2019)
The purpose of the study is to know the relationship between the organizational climate and job satisfaction according to the perception of the personnel assigned to a higher education institution in the state of Tamaulipas, Mexico, in order to generate tangible results that serve as input for the good management of these constructs. The sample of participation was 208 collaborators who answered the organizational climate questionnaire designed by Litwin & Stringer (1968) and the general scale of satisfaction proposed by Warr et al. (1979). In the analysis of the data, descriptive statistics, factor analysis, the Cronbach's Alpha coefficient and Spearman's Rho correlation technique were used to evaluate the association between the factors of the study variables. The main results show that there is a positive and significant relationship between the components of the analyzed variables, which generates empirical knowledge about the relations of the work environment and the satisfaction of people in their work.